Pembuatan Bioetanol Fuel Grade Ethanol (FGE) dari Singkong dengan Proses Dehidrasi Melalui Penyerapan Menggunkan Zeolit Sintesis - Imam Prasetyo; T Towijaya (JURNAL ILMIAH MOMENTUM, 2026)
Bioethanol is an alcohol produced from plants using microorganisms through a fermentation process. Bioethanol itself is an attractive alternative energy source to develop because it is reported in Indonesia and is renewable. Currently, ethanol is widely used. In addition to being used as a fuel mixture, ethanol is also used in the industrial world as a solvent and as a raw material for other chemical industries, such as the production of ethyl acetate. Therefore, bioethanol may be a potential alternative fuel, and much research is being conducted to develop this fuel. This research aims to produce bioethanol fuel grade (FGE) from cassava raw materials through fermentation, distillation, and dehydration using zeolite synthesis. Cassava raw materials were chosen because of their high starch content and abundant availability in Indonesia. The research process included material preparation, fermentation with yeast, distillation at 78°C, and purification through dehydration. The results showed that the ethanol content of the distillate reached 92–95%, and after the dehydration process increased to 99.8%, meeting Fuel Grade Ethanol (FGE) standards. The use of synthetic zeolite has proven to be efficient, environmentally friendly, and regenerable. These results support efforts to develop sustainable renewable energy and reduce dependence on fossil fuels.